Matemática, perguntado por adriialves, 1 ano atrás

a. (–6)² – 12
b. (–5).(+6)–(–3)²
c. (–8)²:(–16)+5
d. (–6)º + (–3)² + (–2)³ . (–1)
e. 3² – 4² – (—2).(–4)
f. (–7)²–(–7).(–6)

Anexos:

Soluções para a tarefa

Respondido por Usuário anônimo
23
a)
(-6)^2-12= \\ 36-12=24

b)
(-5).(+6)-(-3)^2= \\ (-30)-(+9)= \\ -30-9=-39

c)
(-8)^2:(-16)+5= \\ (+64):(-16)+5= \\ -4+5=1

d)
(-6)^0+(-3)^2+(-2)^3.(-1)= \\ 1+(+9)+(-8).(-1)= \\ 1+9+(+8)= \\ 1+8+9=18

e)
3^2-4^2-(-2).(-4)= \\ 9-16-(+8)= \\ 9-16-8= \\ 9-24=-15

f)
(-7)^2-(-7).(-6)= \\ 49-(+42)= \\ 49-42=7
Perguntas interessantes